Determinants of the gap between breastfeeding knowledge and practices in Vietnamese mothers - Nguyen, Tuan T.; Nguyen, Phuong Hong; Hajeebhoy, Nemat (Wiley, 2014)
We conducted this analysis to examine determinants of the knowledge‐practice gap in early and exclusive breastfeeding (BF). In a cross‐sectional survey, we interviewed 10,834 mothers with children aged 0−23 months old in 11 of 63 provinces of Viet Nam about BF practices, knowledge, barriers and support. The knowledge‐practice gap was defined when a mother knew about the benefit but did not perform the corresponding practice. The proportion of mothers with a knowledge‐practice gap in early and exclusive BF was 34% and 66%, respectively. Mothers were ~10% less likely to have a knowledge‐practice gap in early BF if they received BF advice and support from a health worker during pregnancy or at birth (P < 0.05; Poisson regression). The gap, however, was 60%, 140% and 20% more likely to occur among those with hospital delivery, cesarean delivery and BF difficulty, respectively (P < 0.05 for all). For exclusive BF, a 25% reduction in the gap was found if a mother believed that people who are important to her support exclusive BF (P < 0.001). A 5% increase in the gap was found among mothers who were exposed to infant formula advertising daily (P < 0.01). To reduce the knowledge‐practice gap in early BF, programs should focus on strengthening support by health staff and minimizing health‐facility related barriers. For exclusive BF, programs should focus on addressing socio‐cultural barriers.Grant Funding Source: Bill & Melinda Gates Foundation, through Alive & Thrive Initiative, managed by FHI360